Effect of Reablement Strategies targeting Sarcopenia (ReStart-S) on sarcopenic older adults residing in long term care settings: A protocol for cluster randomized trial - Prabal Kumar; Shashikiran Umakanth; Olivier Bruyère; Girish N (Heliyon)
Background: The prevalence of sarcopenia is high among older adults residing in long-term care settings (LTCS). Guidelines to manage sarcopenia cannot be directly implemented among sarcopenic older adults residing in LTCS. Objectives: To examine the effectiveness of a codesigned Reablement Strategies targeting Sarcopenia (ReStart-S) program on muscle parameters, physical performance, blood biomarkers and quality of life among sarcopenic older adults residing in LTCS. Methods: The study is a cluster randomized trial that will take place in LTCS. A total of 78 sarcopenic older adults will be included, selected through convenience sampling, and diagnosed using the Asian Working Group for Sarcopenia 2019 criteria. The LTCS clusters will be randomized into intervention and control groups. The participants in the intervention group will receive the ReStart-S multicomponent exercise intervention twice a week for a total of six weeks, while those in the control group will continue with their usual daily activities. The primary outcome will be grip strength, and the secondary outcomes will include a short physical performance battery, muscle mass, C-terminal agrin fragment, and quality of life as assessed through the sarcopenia and quality of life-Kannada version questionnaire. The outcomes will be measured at week 0, week 6, week 12, and week 18. Conclusion: ReStart-S program if found to be effective could be implemented globally to manage sarcopenia and promote healthy ageing in older adults, enhancing their independence in LTCS.